Pseudo-Goldstone dark matter in a radiative inverse seesaw scenario - K. Kannike; A. Kubarski; L. Marzola; A. Racioppi (Journal of High Energy Physics, 2023)
Abstract We consider a scale-invariant inverse seesaw model with dynamical breaking of gauge symmetry and lepton number. In some regions of the parameter space, the Majoron — the pseudo-Goldstone of lepton number breaking — is a viable dark matter candidate. The bound on the Majoron decay rate implies a very large dilaton vacuum expectation value, which also results in a suppression of other dark matter couplings. Because of that, the observed dark matter relic abundance can only be matched via the freeze-in mechanism. The scalar field which gives mass to heavy neutrinos can play the role of the inflaton, resulting in a tensor-to-scalar ratio r ≲ 0.01 for metric inflation and r ≲ 0.21 for Palatini gravity.